ANALISA HUKUM ATAS PENGATURAN ASET HAK KEKAYAAN INTELEKTUAL SEBAGAI OBJEK JAMINAN FIDUSIA - Santoso, Tasa Gina (Fakultas Hukum Universitas Islam Indonesia, 2024)
The realization for creative economy actors by providing opportunities for their work in the form of Intellectual Property Rights (HKI) assets which can be used as fiduciary collateral with the ratification of Government Regulation Number 24 of 2022 concerning Implementing Regulations of Law Number 24 of 2019 concerning the Creative Economy, creates opportunities to develop the economy in Indonesia with the government's recognition of IPR as collateral that can be guaranteed. It is hoped that this research can be a positive contribution for both the government and banks to implementing IPR as a collateral object. This research uses normative juridical analysis with the problem formulation: First: How do the regulations in Bank Indonesia Regulations with Government Regulation Number 24 of 2022 concerning Implementing Regulations of Law Number 24 of 2019 concerning the Creative Economy provide an opportunity for IPR assets to be used as objects of fiduciary collateral? Second: What is the certainty and position of IPR assets as objects of fiduciary guarantees in Indonesia? The results of this research found that regulations in Indonesia have agreed to stipulate that IPR assets can be used as fiduciary collateral, but in practice until today it is difficult to use IPR assets as fiduciary collateral, as can be seen from Bank Indonesia Regulation No. 9/6/PBI/2007 which does not specifically regulate IPR assets that can be used as collateral objects in banks. The certainty of IPR assets as collateral makes it difficult for banks to provide credit because they are constrained by the limited period of IPR protection. It is hoped that the results of this research will be a consideration for providing guarantees for creative economy actors who have IPR assets that can be pledged as collateral so that they can provide legal certainty for the community.